Exploration of Knowledge Management in Mediating Organizational Culture and Authentic Leadership on Employee Performance at PT Bareksa Investment Portal - Habiburrahman, Tedy; Winarno, Alex; L, Bachruddin Saleh (Formosa Journal of Multidisciplinary Research, 2024)
PT Bareksa is a pioneer of integrated financial and investment marketplace services in Indonesia. Since obtaining an official license from the Financial Services Authority (OJK) in 2016, Bareksa has become a Mutual Fund Selling Agent offering mutual fund products from various trusted investment managers. With a significant market share, Bareksa is trusted by many investors in Indonesia. The purpose of this research is to identify and analyze the influence of organizational culture and authentic leadership on employee performance through knowledge management. This research uses a quantitative approach with a descriptive causality type of research. The number of respondents is 200 people. The data analysis technique used is descriptive analysis and path analysis. The results of the research show that both partially and simultaneously, organizational culture and authentic leadership through knowledge management have a significant impact on improving employee performance. Organizational culture, authentic leadership, and knowledge management are able to explain the level of influence by 67.4%, while the remaining 32.6% is influenced by other factors. Descriptively, all variables are in a very good position. The implication of this research is the need to strengthen organizational culture supported by authentic leadership and applied through knowledge management to encourage performance improvement.